2019
DOI: 10.3390/d11120227
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Amphioxus Branchiostoma californiense (Amphioxiformes: Branchiostomatidae) Adjacent to a Shallow Submarine Hydrothermal System at Banderas Bay (Mexico)

Abstract: Shallow submarine hydrothermal vent systems assume differentiated environmental conditions. Some specimens of Branchiostoma californiense were found in the sediments of the influence area of the shallow hydrothermal venting in Punta Mita. This is the only lancelet species registered for the Mexican Pacific. The meristic and morphometric characteristics of the organisms first collected in unconsolidated sediments of this shallow system were reviewed, in order to determine the species. We confirm that it is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They are exclusively marine, with wide distribution in temperate and tropical waters (Del Moral-Flores et al 2016). They are generally buried in shallow bottoms near the coast and thick sediments (sand, gravel, shell remains), spending most of their lives filtering small organic particles (Rodríguez-Uribe et al 2019). These authors also indicate that some species are occasional swimmers, spending part of their life in plankton, and can inhabit depths greater than 200 m.…”
mentioning
confidence: 91%
“…They are exclusively marine, with wide distribution in temperate and tropical waters (Del Moral-Flores et al 2016). They are generally buried in shallow bottoms near the coast and thick sediments (sand, gravel, shell remains), spending most of their lives filtering small organic particles (Rodríguez-Uribe et al 2019). These authors also indicate that some species are occasional swimmers, spending part of their life in plankton, and can inhabit depths greater than 200 m.…”
mentioning
confidence: 91%
“…Several species were newly described, or their taxonomy has been clarified only recently [2,29,30], and species misidentification or cryptic diversity have been found using molecular approaches or integrative taxonomy [14,[31][32][33][34][35][36]. Moreover, new records of lancelet larvae or adults improved our assessment of species-specific geographical distribution and ecological traits at a range of scales [37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rodríguez-Uribe et al [9] reported for the first time the presence of the amphioxus Branchiostoma californiense in the marine sediments within the influence area of SSHSPM. While Prol-Ledesma et al [10] descriptively reported that small concentrations of macrofauna were observed in sediment samples collected in SSHSPM, nematodes and amphipods were the most abundant.…”
Section: Introductionmentioning
confidence: 99%